Effect of bulb size on selected morphological characteristics of seed stalks, seed yield and quality of onion (Allium cepa L.) seeds - Morozowska Maria; Hołubowicz Roman (Folia Horticulturae, 2009)
In the years 2002 − 2004 research was carried out on the effect of onion (Allium cepa L.) ‘Wolska’ bulb size on selected morphological characteristics of seed stalks, seed yield and quality. Commercial bulbs (vernalised, one-year-old mother bulbs) were divided into three groups: small, medium and large, with diameters of 4.2-5.3 cm, 5.4-6.3 cm and 6.4-8.5 cm, respectively. Then, the bulbs of each group were planted in the field and grown routinely with the purpose of producing seeds. The following characters were measured on the seed stalks: number and height of seed stalks grown out from one bulb, the seed stalks’ diameter at the height of 10 cm above the ground, the diameter of the inflorescence, seed yield from a single stalk and from the entire plant, the weight of 1000 seeds, number of seeds in 1 g, length and width of the seeds, length and width of the embryos, and germination energy and capacity. Our experiments showed a significant influence of bulb size on the number of seed stalks and the inflorescence diameter. It was discovered that the big bulbs gave larger numbers of seed stalks than the seed stalks grown from the medium and small ones. Small bulbs gave seed stalks with smaller inflorescences than the medium and large ones. The bulb size had no effect on the seed stalk height or their diameter when measured at the level of 10 cm above the ground. The bulb size also did not affect seed yield per one seed stalk, but it did affect the seed yield obtained from the entire plant, which was bigger for plants grown from large bulbs in comparison with the small ones. The size of the bulbs had no effect on either the weight of 1000 seeds or the number of seeds in 1 g. It did not affect either the seed and embryo length and width or the seed germination energy and capacity.